Ecological economics of sustainable watershed management - Erickson, Jon D.; Messner, Frank; Ring, Irene, 1961- (Advances in the economics of environmental resources ;, 2007)
The papers in this volume illustrate the power of a scientific approach to ecological economics. Good science is a careful blend of theory and empirical testing. Theory without empirical grounding is of no practical value and random case studies without a theoretical context are not generalizable. The back and forth interplay between theory and evidence is apparent in the modeling exercises, evaluation studies, and policy design described in this book. Watershed management has been chosen as a concrete focus to illuminate the facets of sustainability. It requires both a deep understanding of the natural processes in watersheds and of the societal processes which strongly depend on the natural watershed services. Furthermore, country-specific governance structures need to be considered to fine-tune the design of sustainable watershed policies in order to approach an interaction of society and nature, which ensures a long term use of water resources without adverse effects on society and the environment. This book has accepted the challenge to tackle the complex scientific underpinning of sustainable watershed analysis and management and will reveal basic ecological economic knowledge and methodological approaches in this prominent field of research.